The impact of technology on the structure of employment at the present stage (Economics and region, 2023)
The article analyzes the impact of technology on the labor market in the past, as well as the current state of the labor market and the prospects for its transformation in the near future. The measures that serve as indicators of the level of technological development are identified. The impact of technology on the labor market is characterized. It is found that technological development increases labor productivity, which leads to economic growth. A comparison of the employment structure in technologically advanced countries and technologically backward countries is made. It is found that the employment structure of these two groups of countries differs significantly, and the trends prevailing in the labor markets of the studied groups of countries are also different. The reasons for these differences are clarified. It has been found that technologically backward countries, which are also developing countries, have different labor market conditions from developed countries, lower labor force qualifications and weaker social policies. It was also found that in developed countries, there is no longer a reduction in employment in agriculture, but employment in industry is declining. Common to the labor markets of both groups of countries is an increase in the share of those employed in the service sector. The current state and prospects of transformations in the global labor market are determined. It has been found that global trends are closer to those of developing countries than to the trends prevailing in the labor markets of developed countries.
Keywords: technology; productivity; labor market; industrial revolution; service sector